BRAC Education Program (BEP): progress report, June - November 2003 - BRAC (© BRAC, 2016)
1. BEP logframe analysis 2. School operation 3. Capacity development unit 4. Material development and new initiatives 5. PACE/ADP 6. Government partnership unit 7. Effective programme management 8. Financial report.